Are Novel, Nonrandomized Analytic Methods Fit for Decision Making? The Need for Prospective, Controlled, and Transparent Validation. Issue 4 (1st October 2019) - Eichler, Hans‐Georg; Koenig, Franz; Arlett, Peter; Enzmann, Harald; Humphreys, Anthony; Pétavy, Frank; Schwarzer‐Daum, Brigitte; Sepodes, Bruno; Vamvakas, Spiros; Rasi, Guido
Abstract : Real‐world data and patient‐level data from completed randomized controlled trials are becoming available for secondary analysis on an unprecedented scale. A range of novel methodologies and study designs have been proposed for their analysis or combination. However, to make novel analytical methods acceptable for regulators and other decision makers will require their testing and validation in broadly the same way one would evaluate a new drug: prospectively, well‐controlled, and according to a pre‐agreed plan. From a European regulators' perspective, the established methods qualification advice procedure with active participation of patient groups and other decision makers is an efficient and transparent platform for the development and validation of novel study designs.